Vacuolar Membrane ATPase Activity 21 Predicts a Favorable Outcome and Acts as a Suppressor in Colorectal Cancer - Zhang, Fan; Shen, Hao; Fu, Yating; Yu, Guanyu; Cao, Fuao; Chang, Wenjun; Xie, Zhongdong (Frontiers in Oncology, 2021)
Extracellular and/or intracellular manipulation of pH in tumor may have noticeable potential in cancer treatment. Although the assembly factor genes of V0 domain of the V-ATPase complex are required for intracellular pH homeostasis, their significance in colorectal cancer (CRC) remains largely unknown. Here, we used bioinformatics to identify the candidates from known assembly factor genes of the V0 domain, which were further evaluated by immunohistochemistry (IHC) in CRC and adjacent normal specimens from 661 patients. Univariate and multivariate Cox analyses were used to evaluate factors contributing to prognosis. The effects of variations in the expression of VMA21 on tumor growth were assessed in vitro and in vivo. Of five known assembly factors, only VMA21 showed differential expression between CRC and adjacent normal tissues at both mRNA and protein levels. Patients with high VMA21 expression had higher differentiation grade and longer disease-specific survival (DSS) at stages I–III disease. High VMA21 expression in tumors was also an independent predictor of DSS (hazard ratio, 0.345; 95% confidence interval, 0.123–0.976), with covariates included TNM stage and differentiation grade. VMA21 overexpression decreased CRC growth, whereas VMA21 knockdown increased CRC growth in vitro and in vivo. VMA21 expression suppresses CRC growth and predicts a favorable DSS in patients with stage I-III disease.